2015
DOI: 10.1039/c4qi00158c
|View full text |Cite
|
Sign up to set email alerts
|

Redox and acidic properties of chalcogenido-substituted mixed-metal polyoxoanions: a DFT study of α-[PW11O39ME]4− (M = Nb, Ta; E = O, S, Se)

Abstract: The redox and acidic properties of α-Keggin anions [PW 11 O 39 ME] 4− (M = Nb, Ta; E = O, S, Se) have been investigated by using the density functional theory (DFT) method. The calculated results for the studied clusters are consistent with the hypothesis that the substitution of one O atom by S or Se atoms in polyoxometalates (POMs) modifies the relative energy of the lowest unoccupied molecular orbital, inducing slight changes in the redox properties of POMs. The electronic structures and reduction energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…POMs are nanoscale cluster compounds that are typically composed of higher-valent transition metals (Mo, W, V, Nb, etc. ). Adjusting synthesis conditions can result in variable stoichiometries, including the well-known clusters [Nb 10 O 28 ] 6– , [PW 12 O 40 ] 3– , [P 2 W 15 V 3 O 62 ] 9– , [Mo 6 O 19 ] 2– . Each of these stoichiometries can be classified into different POM structure types and display distinct chemical and physical properties that can be controlled by adjusting the constituent atoms .…”
Section: Introductionmentioning
confidence: 99%
“…POMs are nanoscale cluster compounds that are typically composed of higher-valent transition metals (Mo, W, V, Nb, etc. ). Adjusting synthesis conditions can result in variable stoichiometries, including the well-known clusters [Nb 10 O 28 ] 6– , [PW 12 O 40 ] 3– , [P 2 W 15 V 3 O 62 ] 9– , [Mo 6 O 19 ] 2– . Each of these stoichiometries can be classified into different POM structure types and display distinct chemical and physical properties that can be controlled by adjusting the constituent atoms .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, through the combination of environmental and theoretical analysis, it is found that the electronic structures of [PW 11 O 39 M] n − (M = Nb, Ta) with different doped atoms (O, S, Se) can be modified through the substitution effect (Figure 1I). [ 39 ] The relative energy of the LUMO in [PW 11 O 39 M] n − can be optimized through the substitution of O atoms to S or Se atoms, resulting in enhanced redox properties.…”
Section: Structures Synthesis and Characterizations Of Pom Molecules ...mentioning
confidence: 99%
“…I) Molecular orbital diagram for [PW 11 O 39 M] n− and corresponding derivatives. Reproduced with permission [39]. Copyright 2015, the Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…To attain a better understanding of the basicity of 1_POMs , theoretical calculations were performed by the density functional theory (DFT) method. 33 The results of natural population analyses of the POMs are summarized in Tables S3–S5 †. To investigate the effect of Nb/Ta-substitution on the electron density distribution within the POMs, we compared the natural charges of atoms at equivalent positions in Nb/Ta-substituted POMs ( SiW 11 Nb and SiW 11 Ta ) and non-substituted POM ( BW 12 ).…”
mentioning
confidence: 99%